2009
DOI: 10.1111/j.1365-2966.2009.14545.x
|View full text |Cite
|
Sign up to set email alerts
|

The helium star donor channel for the progenitors of Type Ia supernovae

Abstract: Type Ia supernovae (SNe Ia) play an important role in astrophysics, especially in the study of cosmic evolution. Several progenitor models for SNe Ia have been proposed in the past. In this paper we carry out a detailed study of the He star donor channel, in which a carbon–oxygen white dwarf (CO WD) accretes material from a He main‐sequence star or a He subgiant to increase its mass to the Chandrasekhar mass. Employing Eggleton's stellar evolution code with an optically thick wind assumption, and adopting the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
237
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 197 publications
(248 citation statements)
references
References 61 publications
6
237
4
Order By: Relevance
“…Yoon & Langer (2003) also found that CO WD + He star systems can form a reliable channel that produces SNe Ia. Recently, Wang et al (2009a) systematically explored the evolution of 2600 close WD binaries that include a He MS star or He subgiant, and obtained the parameter spaces for the progenitor of SNe Ia. With a detailed binary population synthesis approach, Wang et al (2009b) suggested that this channel can contribute a SN Ia birthrate of 3 × 10 −4 yr −1 in the Galaxy, and can result in the short delay times ( < ∼ 100 Myr) between the formation of the progenitor systems and the explosions.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Yoon & Langer (2003) also found that CO WD + He star systems can form a reliable channel that produces SNe Ia. Recently, Wang et al (2009a) systematically explored the evolution of 2600 close WD binaries that include a He MS star or He subgiant, and obtained the parameter spaces for the progenitor of SNe Ia. With a detailed binary population synthesis approach, Wang et al (2009b) suggested that this channel can contribute a SN Ia birthrate of 3 × 10 −4 yr −1 in the Galaxy, and can result in the short delay times ( < ∼ 100 Myr) between the formation of the progenitor systems and the explosions.…”
Section: Introductionmentioning
confidence: 93%
“…Finally, if |Ṁ He | is lower thanṀ low , the strong He-shell flashes occur, and no material can be accumulated onto the WD. Summarizing the above prescriptions, the accumulation efficiency of the accreting He can be written as (Wang et al 2009a)…”
Section: Binary Evolution Codementioning
confidence: 99%
“…The predicted amount of accreted material is sufficient for the WD to reach the Chandrasekhar limit. This makes HD 49798 another candidate SN Ia progenitor, should the companion be a C/O white dwarf (Wang et al 2009). SN Ia play a key role in the study of cosmic evolution since they are utilised as standard candles for determining the cosmological parameters (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the calculations, we adopted the stellar OPAL opacities for a low temperature given by Rogers & Iglesias (1992) and Alexander & Ferguson (1994) and take the ratio of the mixing length to the pressure scale height to be 2.0. The overshooting parameter of the He star (with a chemical abundance Y = 0.98, Z = 0.02) is set to 0 (Wang et al 2009). …”
Section: An Example Evolutionary Path To Psr J1802-2124mentioning
confidence: 99%